Ecotourism: Between Economic Importance and Environmental Sustainability Challenges in Najaf Governorate-An analytical study in tourism geography (Eurasian Journal of Media and Communications, 2026)
This study deals with the reality of ecotourism in Najaf Governorate, with a focus on the Najaf Sea Low as an applied model that combines geographical importance and investment opportunities. The researcher aims to prove the role of ecotourism in achieving economic and social integration to a sustainable environment. The study revealed through the analytical method and fieldwork that the Najaf Sea region has unique natural, geological and climatic elements that qualify it to be a tourist pole that supports the local economy and provides diverse job opportunities. Despite this high awareness of economic importance, the results showed serious environmental challenges represented by high levels of pollution, waste accumulation and poor environmental and service planning in tourist sites. The study indicates the need to adopt a comprehensive planning vision that adopts green tourism standards, and enacts environmental laws and control, while enhancing community awareness to ensure the investment of these resources without compromising the rights of future generations.